Not Ready for Prime Time: Financial Reporting Quality After SPAC Mergers - Kim, Jaewoo; Park, Seyoung; Peterson, Kyle; Wilson, Ryan (Management Science, 2022)
We examine the financial reporting quality of special purpose acquisition corporations (SPACs) following a successful merger. We compare a sample of SPACs with completed mergers from 2006 to 2020 to initial public offering (IPO) firms in the same industry covering the same period. Compared with similar IPO firms, SPACs are more likely to restate their financial statements and have internal control weaknesses. We also find that SPACs are more likely to file untimely financial statements, amend previously issued filings, and have comment letters that go more rounds with the Securities and Exchange Commission. This lower reporting quality also results in less informative earnings to investors. Our evidence corroborates concerns from the media, accounting firms, and regulators that SPACs exhibit low financial reporting quality in comparison with IPOs. This paper was accepted by Suraj Srinivasan, accounting.